(untitled) (Revista Científica UCOM Scientia, 2025)
The feminicide that occurs in Paraguay in the year 2024 is a social concern that is increasing year after year. That is why in this case this research focuses on analyzing the damage that feminicide leaves in its wake on children and adolescents, which as a result causes orphans in its wake. It also aims to recognize the psychological damage that femicide causes in children and adolescents and determine the legal situation and state responsibility of children and adolescents in the face of the crime of femicide in Paraguay. Methodologically, for this purpose, a review of the literature was carried out, through a documentary analysis, taking into account the study variables. The most significant results were that it was determined that children and adolescents are unprotected as they are orphaned by acts of feminicide, lacking timely psychological care and strategies that cover their economic needs from the State. In conclusion, it is necessary to have clearer and more precise laws that protect children and adolescents in all their aspects when they become orphans due to feminicide; as well as continue working on the eradication of misogyny, and above all, have the appropriate psychological support for orphans. Likewise, it is proposed to continue with lines of research of this magnitude, to become aware of the social problems that are being experienced and to minimize the consequences